Rapid redesign and effect on clinical workload of a supra-regional burns and plastic surgery service during the COVID-19 pandemic. Issue 2 (February 2022) - Li, Zoe; Leong, Samantha; Malik, Mohammad; Ibrahim, Nader; Sin-Hidge, Claire; Clancy, Rachel; Dobbs, Thomas D.; Jessop, Zita M.; Duncan, Robert T.; Hemington-Gorse, Sarah; Tickunas, Tomas; Yarrow, Jeremy; et al.
Summary: Introduction: In March 2020, South Wales experienced the most significant COVID-19 outbreak in the UK outside of London. We share our experience of the rapid redesign and subsequent change in activity in one of the busiest supra-regional burns and plastic surgery services in the UK. Methods: A time-matched retrospective service evaluation was completed for a 7-week "COVID-19" study period and the equivalent weeks in 2018 and 2019. The primary aim of this study was to evaluate plastic surgery theatre use and the impact of service redesign. Comparison between study periods was tested for statistical significance using two-tailed t -tests. Results: Operation numbers reduced by 64% and total operating time by 70%. General anaesthetic cases reduced from 41% to 7% ( p <0.0001), and surgery was mainly carried out in ringfenced daycase theatres. Emergency surgery decreased by 84% and elective surgery by 46%. Cancer surgery as a proportion of total elective operating increased from 51% to 96% ( p <0.0001). The absolute number of cancer-related surgeries undertaken was maintained despite the pandemic. Conclusion: Rapid development of COVID-19 SOPs minimised inpatient admissions. There was a significant decrease in operating while maintaining emergency and cancer surgery. Our ringfenced local anaesthetic Plastic Surgery Treatment Centre was essential in delivering a service. COVID-19 acted as a catalyst for service innovations and the uptake of activities such as telemedicine, virtual MDTs, and online webinars. Our experiences support the need for a core burns and plastic service during a pandemic, and show that the service can be effectively redesigned at speed.